Analisis Efisiensi Penggunaan Tempat Tidur Pasien Berdasarkan Indikator Barber-Johnson Sebagai Upaya Optimalisasi Pengelolaan Ruang Rawat Inap Di RSPAD Gatot Soebroto - Isnayni, Fildza Alya; Marzuki, Satria Yunas (JURNAL MANAJEMEN PENDIDIKAN, 2026)
ANALYSIS OF THE EFFICIENCY OF PATIENT BED USE BASED ON THE BARBER-JOHNSON INDICATOR AS AN EFFORT TO OPTIMIZE THE MANAGEMENT OF INPATIENT ROOMS AT GATOT SOEBROTO HOSPITAL This study aims to analyze the efficiency of patient bed utilization at Gatot Soebroto Army Hospital based on the Barber-Johnson indicators , which include Bed Occupancy Rate (BOR), Length of Stay (LOS), Turnover Interval (TOI), and Bed Turnover (BTO). This study uses a descriptive quantitative method by analyzing secondary data. room care stay regular during 2020-2024 . Data is processed using a graphical approach Barber-Johnson and compared with The standards of the Ministry of Health of the Republic of Indonesia (2011). The results of the study showed a gradual increase in efficiency from 2020 to 2024. In 2020, bed utilization was not fully efficient with a BOR of 70.46%, LOS of 7.72 days, TOI of 3.24 days, and BTO of 33.41 times per year. Optimal efficiency was achieved in 2024 with a BOR of 75.16%, LOS of 5.45 days, TOI of 1.80 days, and BTO of 50.44 times per year. The index analysis showed that the four indicators are interrelated to form an integrated system, where a decrease in LOS and TOI contributes to an increase in BTO and BOR stability. Factors that influence efficiency include the effectiveness of medical and nursing services, digital information systems, discharge planning , inpatient room readiness, and hospital reputation. This study concludes that the management of inpatient beds at RSPAD Gatot Soebroto has reached an optimal level of efficiency in 2024, with a good balance between capacity , turnover patients , and quality service . The findings of this study confirm importance management patient entry and exit flow as well as management capacity data based as effort optimization room care stay overnight .